Rate and Associated Factors of Suicidal Behavior among Adolescents in Bangladesh and Indonesia: Global School‐Based Student Health Survey Data Analysis - M. Marthoenis; S. M. Yasir Arafat (Scientifica)
Objective. Suicidal behavior among adolescents is a major public health problem that is understudied in South East Asian Muslim-majority countries. We aimed to investigate the rate and associated factors of suicidal behavior among adolescents in Bangladesh and Indonesia. Methods. The Global School-based Student Health Survey data of Bangladesh and Indonesia were used in this study. The data consist of a total of 9052 school-aged students from Bangladesh (2570, 28.4%) and Indonesia (6482, 71.6%). Suicidal behavior was assessed using three questions that measure suicidal ideation, suicidal plan, and suicidal attempts. Results. The overall rate of suicidal behavior (suicidal ideation, suicidal plan, and suicidal attempts) was 8.8%, and no significant difference between the two countries (8.9% in Bangladesh and 8.7 in Indonesia) was observed (p=0.81). Factors that independently increased the likelihood of suicidal behavior include female gender, missed class, physical fight four times or more, experienced bullying, anxiety, loneliness, rarely eating fruit, current alcohol use, and sedentary behavior (p<0.05). Meanwhile, factors that independently decreased the likelihood of suicidal behavior include parental supervision and having close friends, either one, two, three persons, or more (p<0.05). Conclusion. The study revealed rates and risk factors of suicidal behaviors among the school-going adolescents of two Muslim-majority countries in South East Asia. Prevention strategies should be considered guided by the risk factors for school-going adolescents.